FOUR CORNERS: A STRATEGY TO ENHANCE SPEAKING - Rekha Asmara (Universitas Islam Ogan Komering Ilir Kayuagung, 2019)
Speaking plays a vital role in running the process of communication smoothly. By speaking, a learner can produce ideas on mind and deliver it to others through the utterances. In an effort to reach a subtle interaction between two or more speakers, some difficulties may arise because of less having vocabulary knowledge, motivation, or suitable materials. Let alone, students lack confidence and have no supporting environment to practice speaking.These difficulties can hinder students from being fluent and accurate speakers of English. Thus, Four Corners strategy was offered to reduce those difficulties. Four Corners strategy was convinced to enhance the students’ speaking ability